Response to threatening messages in anti-smoking campaigns - Suryaningtyas, Annis Azhar; Sandy, Fadillah; Rahayu, Alya Amali (The Indonesian Journal of Communication Studies, 2023)
The campaign on the risks and dangers of smoking has become prevalent through social media, including the Instagram account @suara_tanpa_rokok. It is known that there are 56 content pieces with a threatening message approach regarding the risks of smoking from @suara_tanpa_rokok between 2021 and June 2023. The messages and responses to these messages are interesting to explore from a health communication perspective. This study employs the Extended Parallel Process Model (EPPM) as its analytical framework. The quantitative content analysis method was chosen for this research. The results indicate that health campaign content utilizing a threatening message approach on the risks of smoking in @suara_tanpa_rokok elicits an 83.9% maladaptive response. The lack of awareness and willingness to quit smoking contribute to the emergence of this response.